Implementasi Program Penyuluhan Stop Bullying sebagai Strategi Peningkatan Pemahaman dan Pencegahan Tindak Bullying Pada Anak di Desa Sambirobyong Kabupaten Kediri - Aprilia, Nirma Putri; Zunairoh, Yuyun; Florensia A; Naufal, Demas; Faza, M. Dihqon (Aktualisasi Pengabdian Masyarakat, 2025)
The Stop Bullying counseling program in Sambirobyong Village, Kayen Kidul, Kediri was implemented by KKN UIN Sheikh Wasil Kediri Year 2025 students as an effort to increase community awareness and understanding, especially children, about the dangers of bullying. Using a Participatory Action Research (PAR) approach, this activity involved parents and children in the planning, implementation, and evaluation stages. The counseling methods included interactive lectures, discussions, simulations, and the showing of educational media in the form of animated videos. The material presented included understanding, forms, impacts, and bullying prevention strategies. The results of the activity showed a significant increase in understanding, children no longer viewed bullying as limited to physical violence, but also verbal, psychological, and social. Participants became more sensitive, dared to refuse, and were able to take the right steps when facing or witnessing bullying. Parents' support and children's active participation were important factors in the success of the program. This counseling has proven to be effective in shaping a safe, inclusive, and bullying-free social environment, and can be replicated in other communities facing similar problems.